SAT-374 Adrenal Incidentaloma Management: Development of a Cost-Effectiveness Tool - Hanna, Fahmy W. F. (J Endocr Soc, 2019)
We developed a cost-effectiveness tool “the Adrenal Incidentaloma Intervention Cost Assessment Tool (AI(2)CAT)”. We developed a novel web-based, electronic Adrenal Incidentaloma Management System (eAIMS). We conducted time & motion study utilising the estimated time managing an individual AI case. This was undertaken for different phases of our work: (i) pre-intervention, (ii) The implementation of case prioritisation strategy + utilisation of eAIMS and (iii) future proactive case identification and streamlining into low- and high-risk groups. Projecting our unit’s case load to a UK-wide context, there could be 50,000 new cases PA/year. Utilising the AI2CAT tool and the time and motion analysis data, demonstrated that introducing the eAIMS system in combination with the MDT prioritisation process (Phase 2) reduced the number of tasks required in the AI management pathway. This resulted in a reduction in the hands-on total time taken (from AI identification to MDT decision) by 48.6%. Utilising standardised staff costs, hands-on time was reduced by 28.2% of total costs/patient. Conclusion: We have developed an electronic management system for AI, together with a cost-effectiveness tool to measure the potential cost implications. The combined approach of using the eAIMS system together with a prioritisation strategy resulted in reduced staff hands-on time and cost per case.